Effects of cell cycle noise on excitable gene circuits. (30th November 2016) - Veliz-Cuba, Alan; Gupta, Chinmaya; Bennett, Matthew R; Josić, Krešimir; Ott, William
Abstract: We assess the impact of cell cycle noise on gene circuit dynamics. For bistable genetic switches and excitable circuits, we find that transitions between metastable states most likely occur just after cell division and that this concentration effect intensifies in the presence of transcriptional delay. We explain this concentration effect with a three-states stochastic model. For genetic oscillators, we quantify the temporal correlations between daughter cells induced by cell division. Temporal correlations must be captured properly in order to accurately quantify noise sources within gene networks.